2020
DOI: 10.1104/pp.20.01255
|View full text |Cite
|
Sign up to set email alerts
|

The H3K27me3 Demethylase RELATIVE OF EARLY FLOWERING6 Suppresses Seed Dormancy by Inducing Abscisic Acid Catabolism

Abstract: H3K27me3 demethylase REF6 suppresses seed dormancy and promotes seed germination by enhancing the catabolism of plant hormone Abscisic acid (ABA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 49 publications
4
35
0
1
Order By: Relevance
“…In contrast, genes marked by triple repressive modifications remained silenced during germination, because REF6 binding is repelled by H3K9me2/CHGm, consistent with previous work(Qiu et al, 2019). Supporting the functional requirement of REF6 to initiate germination, loss of REF6 caused higher seed dormancy (Figure 3 and Figure 3—figure supplement 2)(Chen et al, 2020), connected with decreased expression of many germination-inducible genes. Loss of SUVH4/5/6 also increased dormancy (Figure 6—figure supplement 1) (Zheng et al, 2012), which was associated with increased expression of potential REF6 target genes.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast, genes marked by triple repressive modifications remained silenced during germination, because REF6 binding is repelled by H3K9me2/CHGm, consistent with previous work(Qiu et al, 2019). Supporting the functional requirement of REF6 to initiate germination, loss of REF6 caused higher seed dormancy (Figure 3 and Figure 3—figure supplement 2)(Chen et al, 2020), connected with decreased expression of many germination-inducible genes. Loss of SUVH4/5/6 also increased dormancy (Figure 6—figure supplement 1) (Zheng et al, 2012), which was associated with increased expression of potential REF6 target genes.…”
Section: Discussionmentioning
confidence: 69%
“…We confirmed significant suppression of EDF4 in the ref6 mutant endosperm (Figure 5d), supporting the proposed endosperm-specific function of REF6 during germination (Figure 4a and 4b). REF6 was shown to target the ABA catabolism genes CYP707A1 and CYP707A3 , but not CYP707A2 during seed development(Chen et al, 2020). We also found CYP707A1 and CYP707A3 slightly, but significantly suppressed in ref6 endosperm (Figure 5—figure supplement 3), consistent with the presence of REF6-BS in CYP707A1 and CYP707A3 , but not CYP707A2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abscisic acid plays a crucial role in the dormancy process ( Chen et al, 2020b ; Li et al, 2018 ; Song, Zhu & Yan, 2020 ; Tylewicz et al, 2018 ; Zheng et al, 2018 ). Environmental variations cause fluctuations of endogenous ABA levels in plants, resulting in multifarious physiological responses.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin modification plays an essential role in transcriptional regulation of many physiological processes. In a recent study, Chen et al reported that histone demethylation by the methyltransferase RELATIVE OF EARLY FLOWERING 6 (REF6) reduces seed dormancy by inducing ABA catabolism in seeds [ 102 ]. REF6 catalyzes the lysine (K27) demethylation of histone H3 (H3K27m3), of which methylation is associated with gene silencing.…”
Section: Aba Metabolism and Seed Dormancy Inductionmentioning
confidence: 99%